Dynamic Supply Chain Network Design for Diesel Fuel Consumption in Oil and Gas Fields - Stamatti, Vito (2018)
A dynamic supply chain network (SCN) design problem is addressed in this work to optimally fulfill diesel fuel demands in oil and gas fields. Through a novel mixed integer linear programming (MILP) formulation we seek to determine the location of a group of storage tanks (ST) aiming to fulfill the diesel fuel demand while minimizing the net present value of the overall costs over the planning horizon. We introduce the concept of by the mobile ST, which can be seized of released at any period during the planning horizon. Mo-bile STs can be moved period by period among the grid of potential nodes of the superstructure. An integrated SCN is considered, taking into account all its dis-tinctive characteristics. In fact, a generalized approach is developed allowing for flexible flows across the network, capturing the intertwined nature of deci-sions. Economies of scale governing capital investments and operational costs are reflected in terms of the different types of ST to be optimally selected by the model. Lastly, the service level is assessed through a hybrid indicator composed of the magnitude of the flows and the total time required to fulfill fuel demands. A case study under different scenarios is addressed to show the potentials of the proposed approach and the efficiency of the SCN designs being obtained.